Biomechanical Comparison of Tibial Eminence Fracture Fixation With High-Strength Suture, EndoButton, and Suture Anchor - Barber, F. Alan; Süner, Ganim; Özden, Raif; Davul, Serkan; Hapa, Onur; Sünbüloğlu, Emin; Bozdağ, Ergun (Elsevier BV, 2012)
To biomechanically compare anterior cruciate ligament (ACL) tibial bony avulsion fixation by suture anchors, EndoButtons (Smith & Nephew, Andover, MA), and high-strength sutures subjected to cyclic loading.Type III tibial eminence fractures were created in 49 ovine knees, and 7 different types of repairs were performed. Each repair group contained 7 specimens. The repair groups were as follows: No. 2 FiberWire (Arthrex, Naples, FL); No. 2 UltraBraid (Smith & Nephew); No. 2 MaxBraid (Arthrotek, Warsaw, IN); No. 2 Hi-Fi (ConMed Linvatec, Largo, FL); No. 2 OrthoCord (DePuy Mitek, Raynham, MA); Ti-Screw suture anchor (Arthrotek); and titanium EndoButton. These constructs were cyclically loaded (500 cycles, 0 to 100 N, 1 Hz) in the direction of the native ACL and loaded to failure (100 mm/min). Endpoints included ultimate failure load (in Newtons); pullout stiffness (in Newtons per millimeter); cyclic displacement (in millimeters) after 100 cycles, between 100 and 500 cycles, and after 500 cycles; and mode of failure. Bone density testing was performed in all knees.Bone density was not different among the groups. The EndoButton group had a higher ultimate failure load than the FiberWire, UltraBraid, Hi-Fi, and suture anchor groups (P < .05). The MaxBraid and OrthoCord groups had higher failure loads than the suture anchor group (P < .05). The MaxBraid group also had a higher failure load than the Hi-Fi group (P < .05). Stiffness was not statistically different for the various tested constructs. After 100 cycles, the EndoButton group had less displacement than the FiberWire, UltraBraid, MaxBraid, and Hi-Fi groups (P < .05). The suture anchor group had less displacement than the Hi-Fi and FiberWire groups (P < .05). The displacements of the different tested constructs between 100 and 500 cycles and total displacements after 500 cycles were not statistically different. The predominant failure mode was suture rupture.Under cyclic loading conditions in an ovine model, EndoButton fixation of tibial eminence fractures provided greater initial fixation strength than suture anchor fixation or fixation with various high-strength sutures except for OrthoCord.During initial cyclic loading of ACL tibial eminence fractures, the strength of the repair construct should be taken into consideration because conventional suture repair even with ultrahigh-molecular-weight polyethylene sutures may not provide enough strength.
Keywords: Sheep; Sutures; Biomechanical Phenomena; Tibial Fractures; Weight-Bearing; Arthroscopy; Fracture Fixation, Internal; Random Allocation; Treatment Outcome; Suture Anchors; Animals; Female; Anterior Cruciate Ligament